2013
DOI: 10.1002/oby.20587
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term overeating results in incomplete energy intake compensation regardless of energy density or macronutrient composition

Abstract: Objective To evaluate the effects of overeating (140% of energy requirements) a high-fat low-energy density diet (HF/LED, 1.05kcal/g), high-fat high-energy density diet (HF/HED, 1.60kcal/g), and high-carbohydrate (HC) LED (1.05kcal/g) for 2-days on subsequent 4-day energy intake (EI), activity levels, appetite, and mood. Design and Methods Using a randomized cross-over design, energy expenditure and EI were standardized during overeating. Results In 20 adults with a mean±SD BMI of 30.7±4.6kg/m2, EI was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Studies in adults showed that there may be corrective responses to energy intake variation with a lag time between 3 and 6 d (11,12). It remains unclear if this corrective response is effective for both under-and overconsumption (13) and if it is similar in children. Studies of the association between DED and weight gain in children in freeliving conditions and in the long term have shown varied results.…”
Section: Introductionmentioning
confidence: 94%
“…Studies in adults showed that there may be corrective responses to energy intake variation with a lag time between 3 and 6 d (11,12). It remains unclear if this corrective response is effective for both under-and overconsumption (13) and if it is similar in children. Studies of the association between DED and weight gain in children in freeliving conditions and in the long term have shown varied results.…”
Section: Introductionmentioning
confidence: 94%
“…The prevalence of obesity has progressively risen in all parts of the world during the last decades and has become a main public health concern. It is well-known that the positive energy balance, usually resulted from excessive intake of energy, is the fundamental dietary factor associated with weight gain (1). Assessment of the overall impact of diet is commonly preferred for evaluation of single dietary constituents, such as energy intake.…”
Section: Introductionmentioning
confidence: 99%
“… 20 21 22 23 24 Furthermore, the positive relation between frequency of eating out and higher overall energy intake and weight gain is consistent with experimental data suggesting a low ability to compensate for bouts of overeating by equivalent undereating on other occasions. 25 26 27 28 29 However, almost all data have been collected in the US, 20 21 23 and very little information is available from other countries, 24 especially the low and middle income countries where rates of obesity are rising very rapidly.…”
Section: Introductionmentioning
confidence: 99%